A three-dimensional analytical solution for sandwich pipe systems under linearly varying external pressures. (15th September 2016) - Jin, Zhijiang; Shen, Xiaoli; Yan, Sunting; Ye, Hao; Gao, Zhixin; Chen, Zhanfeng
Abstract: A three-dimensional analytical model is presented to calculate the stress and deformation of a sandwich pipe (SP) system subjected to linearly varying external pressures. Based on a stress function method, an analytical solution for a thick-walled pipe was researched, and then an analytical solution for a SP system was obtained according to the boundary and continuity conditions of stress and displacement. Furthermore, the analytical solution of a SP system was verified by comparing with finite element method (FEM). The results indicate that the stresses from present method (PM) are in a good agreement with that from FEM. Finally, our researches provide a benchmark for approximate or numerical solutions, and are beneficial to evaluate the safety and integrality of SP systems. Highlights: An 3D analytical model for sandwich pipe systems has been proposed. Our predictions are agreement with the results of FEM. Our solution provides a benchmark for numerical and approximate solutions